Exploring Translocation of Omah Java in Pawon Garden, Bogor: A Case Study of Ex-situ Architectural Conservation - Anassya Calistha Dewani; Yusfan Adeputera Yusran (International Journal of Environment, Architecture, and Societies, 2022)
Pawon Garden is a building complex located in Parung, Bogor, consisting of several translocated Javanese vernacular (Omah) buildings. This study aims to determine the process of translocation of Javanese Omah in Pawon Garden Parung in a narrative manner, resulting in knowledge about the translocation of Javanese vernacular buildings as an effort of ex-situ conservation in architectural terms. This study uses a qualitative descriptive approach to show the translocation process of Javanese vernacular buildings, starting from technical specifications, elements, and materials. The building translocation process discussed in this study is divided into three stages: the dismantling process, the translocation process, and the reconstruction process. Several changes to the building occur as a form of adjustment of the building to its new environment and functions. The changes reduce the authenticity of the building. However, most of the elements and structures in the translocated Javanese Omah are still the original components of the original building.